Minat Siswa dalam Mengikuti Kegiatan Ekstrakulikuler Sepakbola di SMPN 2 Purwadadi - Agus Kurnia; Muhammad Mury Syafei; Tedi Purbangkara (Peneliti.net, 2021)
The problem of this research is that the researcher suspected the decrease of students’ interest in extracurricular football activities at SMP Negeri 2 Purwadadi in Purwadadi. This research used quantitative descriptive research as a research design and used a survey method as collecting the data. The data collection technique used a questionnaire instrument and the data were analysis by using descriptive statistics with percentages. The population of this research were student of grade VIII at SMP Negeri 2 Purwadadi. However, the research used the purposive sampling technique along with 30 students as respondents. From the results of this research, it is known that the level of student interest in participating in extracurricular football activities at SMPN 2 Purwadadi states in the